METHODOLOGICAL APPROACHES TO THE CLASSIFICATION OF BIOLOGICAL ASSETS - Akhmetova Salima Seytovna , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article examines methodological approaches to the classification of biological assets. The definition and opinions expressed regarding the concept of classification were considered. A methodological approach to the classification of biological assets was proposed and conclusions were made.